Brueckner Events Oscillations in Solar Transition Region - Sima Zeighami; Ehsan Tavabi (Iranian Journal of Astronomy and Astrophysics)
We study Brueckner event Oscillations in Solar Transition Region (TR), with simultaneous observations from the Si IV 1402 Å spectra and slit-jaw images (SJI) 1400 Å based on the Interface Region Imaging Spectrograph (IRIS) on 2014 August 17, and January 27. Study of these events can significantly help us for understanding the mechanisms of the mass and energy transporting from chromosphere toward TR and corona. We obtained intensity profiles from spectrum perpendicular to the slit in three altitudes from the limb, and then by fitting Gaussian intensity profiles, the transverse fluctuations up to 3200 km altitude along the slit were computed. We observed that Si IV spectra shows blue and red wing enhancements in the line profiles indicating upward and downward twisted. Average of Doppler velocities in the first and second data for the three altitudes were obtained 35 and 80 km/s respectively. The results of wavelet analysis of fluctuations revealed dominant periods of 1.5, 3, 5 minutes. According to our results, it was suggested that the fluctuations in the Brueckner events with one wing enhancement and both wing enhancements, illustrated the swaying and rotational motions of spicules over their axes, respectively. The swaying and rotating motions are responsible for kink and twisted Alfvenic supper and hyper sonic waves propagations, respectively.